Pengaruh Current Ratio dan Debt to Equity Ratio terhadap Net Profit Margin pada Perusahaan Makanan dan Minuman Periode 2020–2024 - Jajuli Jajuli; Monica Sari; Abdul Wahid Alfarizi (Baashima : Jurnal Bisnis Digital, Akuntansi, Kewirausahaan, dan Manajemen, 2026)
This study aims to analyze the influence of the Current Ratio (CR) and Debt to Equity Ratio (DER) on the Net Profit Margin (NPM) of food and beverage sub-sector companies listed on the Indonesia Stock Exchange during the 2020–2024 period. The study employs a quantitative approach using an associative method. The research population consists of 96 companies, while the sample was determined using purposive sampling, resulting in 46 companies serving as the research objects during the observation period. The data used are secondary data in the form of annual financial statements. Data analysis was conducted using descriptive statistics, classical assumption tests, multiple linear regression analysis, the coefficient of determination test, and hypothesis testing (t-test and F-test) with the aid of SPSS version 25. The results indicate that, partially, the Current Ratio has a positive and significant effect on the Net Profit Margin (t = 3.483; p = 0.001). The Debt to Equity Ratio also has a positive and significant effect on the Net Profit Margin (t = 1.975; p = 0.050). Simultaneously, the Current Ratio and Debt to Equity Ratio have a significant effect on the Net Profit Margin (p = 0.003). These findings demonstrate that a company's liquidity condition and capital structure play a role in enhancing its ability to generate net profit; thus, the management of these two financial ratios is a crucial factor in supporting the company's profitability performance.